The gingerbread man: Folk Tale - Choi, HyeJung; Bosiak, Ian; Michelle Park (Seoul : XACT, 2009)
A freshly baked gingerbread man escapes when he is taken out of the oven and eludes a number of pursuers until he meets a clever fox.
H
500
H
Keywords: Folktale; Baking; Gingerbread